Societal Implications of Community-Oriented Policing and Technology - Leventakis, Georgios; Haberfeld, M. R. (SpringerBriefs in Policing, 2018)
Community-Oriented Policing; Policing and Society; Police Science; Police-Community Relations; Police Legitimacy; Technology and Ethics; Fear of Crime; Crime Detection